COVID-19 induced aorto duodenal fistula following evar in the so called "negative" patient. (February 2023) - Traina, Luca; Mucignat, Marianna; Rizzo, Roberta; Gafà, Roberta; Bortolotti, Daria; Passaro, Angelina; Zamboni, Paolo
Objectives: Since October 2019, SARS-CoV-2 pandemic represents a challenge for the international healthcare system and for the treatment and survival of patients. We normally focus on symptomatic patients, and symptoms can range from the respiratory to the gastrointestinal system. In addition, we consider patients without fever and respiratory symptoms, with both a negative RT nasopharyngeal swab and lung CT, as a "Covid-19 negative patient." In this article, we present a so called Covid-19 "negative" patient, with an unsuspected vascular clinical onset of the viral infection. Methods: An 80 y.o. man, who previously underwent endovascular aortic repair for an infrarenal abdominal aortic aneurysm, presented to our department with an atypical presentation of an aorto-enteric fistula during the pandemic. While in hospital, weekly nasopharyngeal swab tests were always negative for SARS-CoV-2. However, the absence of aortic endograft complications, the gross anatomy of duodenal ischemic injury, and the recent history of the patient who lived the last months in Bergamo, the Italian city with the highest number of COVID-19 deaths, lead the senior Author to suspect an occult SARS-CoV-2 infection. The patient underwent to resection of the fourth portion of the duodenum and the first jejunal loop, with subsequent duodenum–jejunal latero-lateral anastomosis and the direct suture of the aortic wall. The intestinal specimen was investigated as suspected SARS-CoV-2 bowel infection by the means of immune-histochemistry (IHC). An ileum sample obtained in the pre-COVID-19 era was used as a control tissue. Results: The histological analysis of the bowel revealed sustained wall ischemia and liponecrosis of the duodenal wall, with intramural blood vessels thrombosis. Blood vessel endotheliitis and neo-angiogenesis were also observed. Finally, the IHC was strongly positive for SARS-CoV-2 RNA and for HLA-G presence, with a particular concentration both in blood vessels and in the intestinal villi. The control tissue sample was not positive for both SARS-CoV-2 and HLA-G. Conclusions: Coronavirus pandemic continues to be an international challenge and more studies and trials must be done to learn its pathogenesis and its complications. As for thromboembolic events caused by SARS-COV-2, vascular surgeons are involved in treatment and prevention of the complications of this syndrome and must be ready with general surgeons to investigate atypical and particular cases such as the one discussed in this article.